Inovasi Kurikulum dan Pembelajaran PAI Pada Masa Pandemi Covid-19 - Rinjani , Cintia; Arifmiboy, Arifmiboy (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2021)
At this time all countries in all corners of the world are being hit by a major disaster caused by the Covid-19 virus. The Covid-19 virus has had an impact on the world of education, including Islamic religious education. The government implemented large-scale social restrictions (PSBB) in most areas in Indonesia, in this case the Ministry of Education and Culture decided students to study at home with parental guidance. With the implementation of distance schools, teachers are required to be creative and innovative in working on the curriculum according to the existing situation and needs. The purpose of this research is to study the curriculum and learning of Islamic education during the Covid-19 period. This study uses a qualitative descriptive method that is to analyze and then clearly describe the problem that comes from a literature review. The results of the research are: 1) Curriculum innovation is a necessity that cannot be accounted for, especially for different discussions like the current one in the Covid-19 pandemic. 2) The curriculum components are objectives, learning materials, learning processes, Learning Strategies and Learning Evaluation, and by utilizing information and communication technology.